1998
DOI: 10.2166/wst.1998.0594
|View full text |Cite
|
Sign up to set email alerts
|

Molecular microbial ecology of nitrification in an activated sludge process treating refinery wastewater

Abstract: The diversity of autotrophic ammonia-oxidizing bacteria (AOB) of the b-subdivision of the class Proteobacteria was investigated in a laboratory-scale denitrification-nitrification bioreactor (DNB) treating a synthetic waste stream. 16S ribosomal RNA (rRNA) gene sequences were amplified from DNA extracted from the oxic DNB sludge. Comparative analysis of the rRNA sequences revealed considerable diversity among the AOB-like sequences. The majority of sequences recovered were related to Nitrosomonas spp. but a sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 0 publications
4
26
0
Order By: Relevance
“…Probes were labeled with fluorescein isothiocyanate, tetramethyl rhodamine isothiocyanate, or indocarbocyanine and were obtained commercially (Genosys, Cambridge, United Kingdom, or ThermoHybaid, Ulm, Germany). A calibration of cell numbers against microcolony dimensions was undertaken using Nso190 (S-F-bAOB-0189-a-A-19), Nsm156 (S-G-Nsm-0155-a-A-19), and Nsv443 (S-G-Nsp-0443-a-S-19) (29) and Nsm641 (S-*-Nsm-0641-a-A-23), a probe specific for the dominant AOB 16S rRNA gene sequence recovered from a laboratory-scale reactor (6). The probes used for counts were Nso1225 (S-F-bAOB-1224-a-A-20), Nso190 (S-F-bAOB-0189-a-A-19), Nsm641 (S-*-Nsm-0641-a-A-23), and Eub338 (S-D-Bact-0338-a-A-18).…”
Section: Activated Sludge Plantsmentioning
confidence: 99%
“…Probes were labeled with fluorescein isothiocyanate, tetramethyl rhodamine isothiocyanate, or indocarbocyanine and were obtained commercially (Genosys, Cambridge, United Kingdom, or ThermoHybaid, Ulm, Germany). A calibration of cell numbers against microcolony dimensions was undertaken using Nso190 (S-F-bAOB-0189-a-A-19), Nsm156 (S-G-Nsm-0155-a-A-19), and Nsv443 (S-G-Nsp-0443-a-S-19) (29) and Nsm641 (S-*-Nsm-0641-a-A-23), a probe specific for the dominant AOB 16S rRNA gene sequence recovered from a laboratory-scale reactor (6). The probes used for counts were Nso1225 (S-F-bAOB-1224-a-A-20), Nso190 (S-F-bAOB-0189-a-A-19), Nsm641 (S-*-Nsm-0641-a-A-23), and Eub338 (S-D-Bact-0338-a-A-18).…”
Section: Activated Sludge Plantsmentioning
confidence: 99%
“…Different physico-chemical treatments have been employed in recent years for the removal of nitrogenated and organic compounds in coke wastewater (Ghose 2002;Mimhalma and De Pinho 2004). Biological treatments, widely used for domestic wastewater, have been extended to industrial wastewater over the last few decades (González et al 2001a, b;Ballinger et al 1998;Fang et al 1993;Grupta and Sharma 1996;Hirata et al 2001) and also to coke oven wastewater (Jeong and Chung 2006;Lee et al 2005;Ning et al 2005;Papadimitriou et al 2006;Qi et al 2007;Yamagishi et al 2001). In this latter case, very high hydraulic residence times are needed due to the slow biodegradability and toxicity of some of the compounds present in such wastewater.…”
Section: Introductionmentioning
confidence: 99%
“…FISH results revealed that both Nitrosomonas and Nitrosospira genera were found to be present in all samples during the monitoring period under changing conditions, therefore, one can interpret that one type of ammoniaoxidizing species cannot necessarily overpopulate on others, both can survive together on the contrary to Ballinger et al [25] who reported that different sub-populations of AOB may predominate under different operational regimes. Unfortunately, quantification could not be done in this study since most of the AOB form aggregates and their counts under epifluorescence microscopy would have resulted in unreliable data.…”
Section: Detection Of Aob In Biological Treatment Reactor Samples By mentioning
confidence: 67%